Smart Health Ledger: Transforming Healthcare Finance Through Blockchain-Powered Data Systems - G, Koadeeswaran; S, Shriram; D, Chitradevi; S, Theyagaraja; P, Sugash; K, Dhivakar; T, Karthikeyan (Journal of Neonatal Surgery, 2025)
The healthcare industry faces critical financial management issues including delayed reimbursements, billing errors, and fraud, largely due to fragmented and outdated systems. This paper proposes the Smart Health Ledger (SHL)—a blockchain-powered platform integrating smart contracts and machine learning to automate and secure healthcare financial processes. SHL utilizes a permissioned blockchain for immutable record-keeping and IPFS for efficient off-chain document storage. A multiscale context integration module enables accurate fraud detection using sequential and historical data patterns. Machine learning models like BiLSTM demonstrated a fraud detection accuracy of 94.8%, with billing errors reduced by 30% and claim cycle time cut by 70%. The system enhances trust, transparency, and operational efficiency across payers, providers, and patients. SHL represents a significant advancement in healthcare finance, promoting a secure, data-driven, and interoperable digital ecosystem. Future work will focus on scalability, compliance, and legacy system integration